Immagini del denaro: scambio, temporalità e dispendio nel cinema - Dario Giugliano (Rivista di Estetica, 2011)
This essay discusses the matter of the cinematography, with the analysis of Elio Petri’s film and novel, La proprietà non è più un furto, in the background. These works are paradigmatic as to a fundamental aspect of the cinematography, that connects it with the mechanism of the money. This mechanism, as every other human product, is the effect of a projection of the humanistic ideology. For this ideology the system of exchange is the ground of the monetary circulation. Criticizing this idea, this essay individualizes a correspondence between production (capture) of images in the cinema and monetary circulation (considered in his totality of displacement and original theft).